Systematic review of topical interventions for the management of odour in patients with chronic or malignant fungating wounds. Issue 1 (February 2023) - Gethin, G.; Vellinga, A.; McIntosh, C.; Sezgin, D.; Probst, S.; Murphy, L.; Carr, P.; Ivory, J.; Cunningham, S.; Oommen, A.M.; Joshi, Lokesh; Ffrench, C.
Abstract: Chronic wounds adversely affect the quality of life of individuals and odour is a well-recognised associated factor. Odour can affect sleep, well-being, social interactions, diet and potentially wound healing. This systematic review aims to examine the effectiveness of topical interventions in the management of odour associated with chronic and malignant fungating wounds. A systematic review guided by PRISMA recommendations of randomised controlled trials where odour intensity/odour is the primary outcome was undertaken. Inclusion criteria were adults (18 years and over) with chronic venous, arterial, diabetic or pressure ulcers or with malignant fungating wounds where odour has been managed through topical application of pharmacological/non-pharmacological agents. Searches were conducted in CENTRAL, CINAHL, EMBASE, MEDLINE, Scopus, and Web of Science. Eligibility screening, risk of bias assessment and data extraction was completed by authors working independently. Searches retrieved 171 titles and abstracts (157 post de-duplication). Thirteen studies were retained for full text review of which five ( n  = 137 individuals) examining the following treatments remained: metronidazole ( n  = 4), silver ( n  = 1). Meta-analysis was not possible but individual studies suggest improved outcomes (i.e., reduced odour) using metronidazole. Treatment options to manage wound odour are limited and hampered by lack of clinical trials, small sample sizes, and absence of standardised outcomes and consistent measurement. Whereas metronidazole and silver may have a role in controlling wound odour, robust and well-designed interventions with rigorous procedures and standardised odour outcomes are necessary to evaluate their contribution. Highlights: Disparity in odour evaluation means difficult translation of research to practice. Increased statistical robustness is required in future odour research. Treatments to manage wound odour are limited and hindered by lack of research. Tentative evidence for metronidazole, but not seen to improve quality of life.